AAAS atlas of population & environment - Harrison, Paul 1945-; Pearce, Fred.; American Association for the Advancement of Science (Berkeley, CA University of California Press, 2000)
This volume discusses and illustrates the effects of the world's population on natural resources, land use, atmosphere, chemicals, wastes, ecosystems, and biodiversity. It is filled with high-quality maps, charts, and informative illustrations."--"Outstanding Reference Sources," American Libraries, May 2002.
At head of title: American Association for the Advancement of Science.
Includes bibliographical references and index.
Keywords: Population -- Environmental aspects